Molecular profiling and phenotypic evaluation of thermo-sensitive genic male sterility genes for high-yielding rice hybrids (Oryza sativa L.) - B. Nagendra Naidu; Manonmani Swaminathan; Nivedha Rakkimuthu; Pushpam Ramamoorthy; Kumaresan Dharmalingam; Raveendran Muthurajan; Selvi Duraisamy; Tushar Arun Mohanty; Bonipas Antony John (PeerJ)
Temperature-sensitive genic male sterility (TGMS) is crucial for boosting rice productivity and ensuring food security. In this study, we evaluated the morphological traits and genetic diversity of 57 rice TGMS lines under fertility-inducing (Gudalur) and sterility-inducing (Coimbatore) environments. Significant variations were observed in yield and floral characteristics, with flowering times ranging from 62.3 to 152.0 days. Lines such as TNAU 16S and TNAU 93S exhibited shorter plant heights and durations, along with higher numbers of productive tillers, making them promising candidates for hybrid breeding. Molecular profiling revealed that the tms8 gene was the most prevalent across the lines, with some carrying combinations of two or more TGMS genes. TNAU 38S and TNAU 60S possessed all four TGMS genes, ensuring stable sterility. These lines showed low fertility temperatures at Gudalur and low sterility temperatures at Coimbatore, indicating optimal conditions for hybrid seed production. Floral characteristics in lines like TNAU 19S, TNAU 126S-1 and TNAU 126S-2 were favorable, with total sterility under sterility-inducing conditions and increased fertility under fertility-inducing conditions, making them ideal for hybridization. For short-duration, semi-dwarf hybrids, TNAU 93S and TNAU 16S were identified as suitable female parents. Overall, this study highlights the significance of TGMS gene combinations for stable male sterility expression and identifies lines such as TNAU 37S, TNAU 60S and TNAU 85S as optimal for high-yielding two-line rice hybrids. The findings emphasize the potential for developing diverse, stable hybrids that can contribute to improved rice productivity and global food security.